POSITIONS AND STABILITY OF LIBRATION POINTS IN THE RADIATING AND OBLATING BIGGER PRIMARY OF CIRCULAR RESTRICTED THREE-BODY PROBLEM (FUDMA JOURNAL OF SCIENCES, 2020)
This paper investigates the positions and stability of libration points in the framework of the circular restricted three-body problem for the systems: Luyten726-8 and HD98800. The position of the third body is contained in the plane direction above and below the oblate bigger and smaller primaries. It is observed that presence of radiations and oblateness of the primary affect the stability of the libration points. Considering the range of stability and instability, that is  and , the libration points are respectively stable and unstable for HD98800 and Luyten 762-8 systems. Our results show that, all the roots are real, and for each set of values, there exist at least a positive real part and hence in the Lyapunov sense, the stability of the libration points are unstable for the systems HD98800 and Luyten 762-8.
Keywords: Luyten726-8, Libration points, Radiations, Oblateness